2011
DOI: 10.3390/molecules16032726
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Their Constituents: Anticonvulsant Activity

Abstract: A literature-based survey of plants species and their essential oils with anticonvulsant activity was carried out. As results, 30 species belonging to 13 families and 23 genera were identified for their activities in the experimental models used for anticonvulsant drug screening. Thirty chemical constituents of essential oils with anticonvulsant properties were described. Information on these 30 species is presented together with isolated bioactive compound studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 51 publications
0
59
1
2
Order By: Relevance
“…Normally C. validus is found in mountainous grasslands and also in the high-rainfall areas of South Africa where it is known to grow in wet sites, along roads and on the margins of tree communities [8]. It is widespread in the Eastern Cape and is often used as durable thatch [4,8]. C. validus oil is pure therapeutic quality aromatherapy essential oil that is produced by using wild-crafted plants and traditional methods from South Africa [9].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally C. validus is found in mountainous grasslands and also in the high-rainfall areas of South Africa where it is known to grow in wet sites, along roads and on the margins of tree communities [8]. It is widespread in the Eastern Cape and is often used as durable thatch [4,8]. C. validus oil is pure therapeutic quality aromatherapy essential oil that is produced by using wild-crafted plants and traditional methods from South Africa [9].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This species belongs to the Poaceae family and has been described as a tufted perennial with culms up to 2.4 m tall. Normally C. validus is found in mountainous grasslands and also in the high-rainfall areas of South Africa where it is known to grow in wet sites, along roads and on the margins of tree communities [8]. It is widespread in the Eastern Cape and is often used as durable thatch [4,8].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Previous studies have indicated that the extract of this plant showed anticonvulsant potentials in many models of convulsion and lobeline isolated from the leaf of L. nicotianaefolia demonstrated significant anticonvulsant activity [29]. Considering the fact that it was just the infusion extract that was used in this study, extraction with other solvents such as ethanol would probably have demonstrated greater anticonvulsant activity because more bioactive substances would be extracted.…”
Section: Discussionmentioning
confidence: 96%
“…A. suaveolens is a succulent, annual herb growing 20-50 cm tall. It is a short-lived perennial herb that stays erect, bushy and can grow till 80 cm [6]. The major components are linalool, 2-decan-5-olide, and linalyl acetate [9] (Fig.…”
Section: A Suaveolensmentioning
confidence: 99%
“…The active constituents in plants show a direct pharmacological action on our body including various organs, having same mechanism of action as that of synthetic drugs [5]. Many essential oils extracted from plants have a significant effect on seizures by having a calm and relaxing effect [6].…”
Section: Introductionmentioning
confidence: 99%